Healthcare attendance patterns by pregnant women in Durban, South Africa - S. Sibeko; J. Moodley (South African Family Practice)
Background: High rates of perinatal mortality and morbidity and maternal mortality in South Africa remain a major problem. The Saving Mothers and Saving Babies Reports identified patient-related factors as possible causes. Among the patient-related factors was non-attendance, or attendance late in pregnancy, for antenatal care in public hospitals. It would appear that pregnant women confirm their pregnancies by visiting general practitioners, but do not attend antenatal care in the public sector. The aim of this study was to determine healthcare attendance patterns among pregnant women in Durban, South Africa.